2023
DOI: 10.1186/s40359-023-01099-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychological correlates of perceived loneliness in college students before and during the COVID-19 stay-at-home period: a longitudinal study

Abstract: Background Loneliness is increasingly acknowledged as a serious public health issue. This longitudinal study aimed to assess the extent to which psychological distress and alexithymia can predict loneliness among Italian college students before and one year after the COVID-19 outbreak. Methods A convenience sample of 177 psychology college students were recruited. Loneliness (UCLA), alexithymia (TAS-20), anxiety symptoms (GAD-7), depressive symptom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
(113 reference statements)
0
3
0
Order By: Relevance
“…Finally, several nonadaptive personality traits including negative affectivity and detachment were related to higher levels of depression, anxiety, and stress during the COVID-19 pandemic [10,32].…”
Section: Introductionmentioning
confidence: 92%
“…Finally, several nonadaptive personality traits including negative affectivity and detachment were related to higher levels of depression, anxiety, and stress during the COVID-19 pandemic [10,32].…”
Section: Introductionmentioning
confidence: 92%
“…Finally, several nonadaptive personality traits including negative affectivity and detachment were related to higher levels of depression, anxiety, and stress during the COVID-19 pandemic [10,37].…”
Section: Introductionmentioning
confidence: 92%
“…Notably, loneliness has been associated with education and memory complaints [8]. University students, in particular, have been the focus of loneliness research for decades [9][10][11][12]. Studies have indicated that over 35% of university students experience loneliness, which is positively correlated with depression and anxiety [13].…”
Section: Introductionmentioning
confidence: 99%